Critical thinking dispositions and self-esteem among nursing students - Hng, SH; Brenda, BJ; Ngu, ZL (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Critical thinking skill is an important skill for nurses to make a better clinical decision in providing safe care. Critical thinking dispositions development is supported with sufficient self-esteem. The present study aimed to measure the level of critical thinking disposition and self-esteem among undergraduate nursing students in a public university in Malaysia. A cross-sectional study was carried out in a university involving 99 students. Data were collected by self-report questionnaires and analysed quantitatively. A total of 97% of the nursing student had a high level of critical thinking dispositions. Almost¾3/4 of the students had a moderate level of perceived self-esteem (74.7%). The critical thinking dispositions were significantly related to perceived self-esteem (p<0.044). Overall, the nursing student of this study had high critical thinking disposition and moderate self-esteem, which is very important for them to become a good nurse with critical thinking skill in the future.